Shop gevaar: a socio-legal critique of the governance of foreign national spaza shopkeepers in South Africa - Gastrow, Vanya (My University, 2017)
Just over ten years ago on night of the 28th of August 2006, angry mobs took to the streets of Masiphumelele township outside Fish Hoek, near Cape Town, and attacked and looted foreign national spaza shops in the neighbourhood. The attacks shocked the city, and prompted the provincial government to initiate an intervention to address the underlying causes of the violence. The outcome comprised an agreement between foreign national and South African spaza shopkeepers that permitted foreign nationals to return on condition that they did not open any new shops in the township. These mediation efforts comprised the beginning of many governance interventions in Cape Town and across the country that were aimed at curtailing foreign national spaza shops in South Africa. This thesis examines formal and informal attempts to govern foreign national spaza shops in South Africa, and seeks to understand what they reveal about the nature of politics in South Africa, as a postcolonial and developing country. In doing so it locates itself in the theoretical framework of law and society, as it examines legal phenomena from a social science perspective. Its findings are based on case study methodology involving qualitative interviews with key participants and stakeholders, as well as document collection, participant observation, and media reports. The research finds that many governance actors’ anxieties towards foreign national spaza shops relate less to shopkeepers’ particular activities and more to South African traders’ abilities to incite local socio-economic discontent against these shops, and thereby threaten political establishments. However, governance interventions rarely unfolded as intended due to resistance by competing interest groups who sought to advance their private economic concerns rather than public and political rights. This invokes features of Hannah Arendt, Michel Foucault and Giorgio Agamben’s theories of the ‘social’ or ‘biopolitics’, which argue that the entry of economic concerns into the political sphere is characteristic of the modern age. The thesis therefore reflects on Arendt, Foucault and Agamben’s theories in assessing what governance efforts reveal about the nature of South Africa’s political sphere. It finds that the social realm in South Africa differs from their accounts in two significant respects. First, the social sphere is conflicted between various economic goals – with parties seeking to foster basic life and sustenance, as well as to advance the emancipation of citizens from the colonial legacies of apartheid through economic mobility and opportunity. This makes finding a path to advance overall economic advancement in the country more difficult and contentious.
Thesis presented for the degree of Doctor of Philosophy in the Faculty of Humanities, at the University of the Witwatersrand, July 2017
Keywords: Immigrants--South Africa--Economic conditions; Entrepreneurship--South Africa; Informal sector (Economics)--South Africa